Pesan Jurnalisme Profetik di Harian Republika - Muhammad - Subarkah; Nani Nurani Muksin (Sahafa Journal of Islamic Communication, 2022)
ABSTRAKPenelitian ini bertujuan untuk menganalisis dan mendeskripsikan gagasan serta  praktik komunikasi pesan jurnalisme profetik di Republika. Teknik penelitian ini menggunakan studi fenomenologi yang bersifat deskriptif-kualitatif dengan melakukan cara wawancara dan studi pustaka. Hasil dari penelitian ini yaitu gagasan dari jurnalisme profetik yang dipraktikkan Republika dapat dikatakan merupakan salah satu bentuk pengayaan dari jurnalisme di Indonesia yang ditambahi ide transedensi dari dakwah para nabi yakni bersifat jujur, komunikatif, pesan dapat dipercaya, dan cerdas.  Hal ini dilihat dari jejak karya jurnalisme Republika yang berdiri semenjak tahun 1993. Dalam rentang waktu selama itu, Republika yang didirikan sebagai media umum yang peduli pada aspirasi umat Islam, konsisten melaksanakan gagasan jurnalisme profetik dalam setiap beritanya. Jurnalisme dipraktikkan tidak hanya mengikuti aturan etis dan teknis jurnalistik, tapi diperkaya dengan gagasan kepedulian kepada nilai transendensi yang hal ini adalah ajaran Islam. Salah satu hal tersebut misalnya ketika Republika bersikap atas isu judi SDSB yang dilakukan secara konsisten dari awal keberadaan  media ini hingga masa sekarang ketika terjadi gelombang perubahan dari media konvensional ke media baru. ABSTRACTThis study aims to analyze and describe the ideas and practices of communicating prophetic journalism messages in Republika. This research technique uses a descriptive-qualitative phenomenological study by conducting interviews and literature studies. The result of this research is that the idea of prophetic journalism practiced by Republika can be said to be a form of enrichment of journalism practices in Indonesia which is added to the idea of transcendence from the da'wah of the prophets, namely being honest, communicative, trustworthy, and intelligent. This can be seen from the traces of Republika's journalism work, which was founded in 1993. During that time, Republika, which was established as a public media that cares about the aspirations of Muslims, has consistently implemented the idea of prophetic journalism in every news report. Journalism is practiced not only following the ethical and technical rules of journalism, but enriched with the idea ofcaring for the transcendent value which is Islamic teachings. One of these things, for example, was when Republika acted on the issue of SDSB gambling which was carried out consistently from the beginning of this media's existence to the present when there was a wave of change from conventional media to new media.